Оценка свойств горных пород при перфораторном бурении и эффективности работы коронок по состоянию твердосплавного вооружения после амортизации инструмента - Линенко-Мельников, Ю.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
In the article the specified data defining the properties of rocks in a bore-hole based on the coefficient of percussion drill ability К are resulted in view of the disturbers caused by the arisen zone of residual pressure and cracks of pre-destruction; the method of the boring tool researches is offered basing on the condition of its hard-alloy supply after drilling with use of digital cameras; it is shown, that using of hard-alloy inserts of cutting type on periphery of pin bits essentially increase their resistance; mechanism of rock’s destruction by pin bits is considered, which allows to improve the tool and modes of drilling.